An Iterative Decomposed Piecewise-Linear Model Description. (7th July 2009) - Jimenez-Fernandez, Victor; Hernandez-Martinez, Luis; Sarmiento-Reyes, Arturo
Abstract : A model description for the representation of one-dimensional piecewise-linear characteristics is presented. The model can be denoted as a decomposed one, because the independent and dependent variables of the PWL characteristic are treated separately. It is also called iterative, because the particular representation of each segment of the PWL characteristic depends on the value of only one parameter included in the mathematical formulation, it gives the possibility of modeling both, univalued and multivalued PWL characteristics.